Enhancing self-esteem among low-achieving adolescents: insights from the role of disputation technique - Rithaudin, Mohamad Farieq Danieal; Ahmad, Noorlila; Abu Bakar, Abu Yazid (Society of Psychology and Education, 2022)
Students' thoughts are crucial for academic motivation and learning. This research aims to determine the influence of the disputation technique on a student's self-esteem with low academic achievement. The sample was recruited using purposive sampling and selected based on predetermined criteria. The study conducted six counseling sessions, the observation list, and the Rosenberg Self-Esteem Scale through action research stages. The data were then analyzed using descriptive and content analysis. This study demonstrates the symptoms of low self-esteem among student. The outcome revealed that the student's self-esteem has improved within the duration and treatment. This result suggests that using the disputation technique efficiently increases students' self-esteem with low academic performance through cognitive, emotional, and behavior analysis.